SKRINING JAMUR KUKU PADA NELAYAN - Fahmi, Norma Farizah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Onychomycosis is a fungal infection of the nails caused by fungus, yeast, or mold. The most common causes of onychomycosis are Trichophyton spp, Microsporum spp, Asperillus spp, Epidermophyton floccosum, Candida albicans, Rhizopus spp, Penicillium. This study was a descriptive study using cross sectional method. The sample used was 30 samples from the total population from January to March. The research was conducted at the Microbiology Laboratory of STIKes Ngudia Husada Madura. The results obtained from this study indicated that 27 samples (100%) were positive for the presence of onychomycosis-causing fungi,Onychomycosis infection in fishermen can be caused by a lack of complete Personnel Protective Equipment (PPE) use and a lack of healthy living habits, such as washing hands with soap and cutting nails every week. This study conducted in the Parasitology Laboratory of STIKes Ngudia Husada Madura showed that the result of research on fishermen’s nail in the village of Sepulu, Bangkalan Regency were declared positive with a percentage of 100% (Aspergillus spp, Tricophyton spp, Candida albicans, Rhizopus spp, Penicillium).